Radiological Differential Diagnoses Based on Cardiovascular and Thoracic Imaging Patterns: Perspectives of Four Large Language Models - Pradosh Kumar Sarangi; Aparna Irodi; Swaha Panda; Debasish Swapnesh Kumar Nayak; Himel Mondal (Indian Journal of Radiology and Imaging, 2024)
Background Differential diagnosis in radiology is a critical aspect of clinical decision-making. Radiologists in the early stages may find difficulties in listing the differential diagnosis from image patterns. In this context, the emergence of large language models (LLMs) has introduced new opportunities as these models have the capacity to access and contextualize extensive information from text-based input.